The Correlation between Matrix Metalloproteinase-9 Point-of-Care Immunoassay, Tear Film Osmolarity, and Ocular Surface Parameters - Min-Ji Kang; Hyun Seung Kim; Man Soo Kim; Eun Chul Kim (Journal of Ophthalmology)
Background. Dry eye disease is a multifactorial disease that is difficult to diagnose due to multiple causative factors. The study aimed to evaluate the correlations between tear film matrix metalloproteinase-9 (MMP-9), tear film osmolarity, and ocular surface parameters in patients with dry eyes. Methods. We performed a retrospective chart review for patients diagnosed with dry eye and investigated if associations existed amongst noninvasive tear breakup time (NIBUT); corneal staining scores; and MMP-9 grade, tear film osmolarity, and Schirmer’s test I results. Results. Twenty-four eyes of 24 patients were enrolled in the current study. The grade of MMP-9 (0–4) was positively correlated with tear film osmolarity (p=0.027). However, neither qualitative (positive or negative) nor quantitative (grade 0–4) measurements of MMP-9 correlated with any other ocular surface parameters. The osmolarity in the positive corneal staining group was significantly higher than that in the negative group (321.6 ± 19.261 and 299.89 ± 16.213, respectively; p=0.018). None of the other ocular surface parameters were correlated with tear film osmolarity. Conclusion. Tear film MMP-9 may be an indicator for tear film osmolarity, or vice-versa. Moreover, osmolarity may have a correlation with corneal staining in patients with dry eye. Tear film MMP-9 and osmolarity tests can be helpful and convenient evaluation tools for identifying inflammation in dry eye disease in clinical practice.